PELATIHAN KAJIAN ANALISIS SASTRA MEMBANGUN KETERAMPILAN DIRI DENGAN KEMAMPUAN MENGANALISIS IMAJINASI SASTRA BAGI MAHASISWA IKIP PGRI SEMARANG - Ambarini AS; Harjito IKIP PGRI Semarang; Nazla Maharani Umaya (E-Dimas: Jurnal Pengabdian kepada Masyarakat, 2010)
AbstrakThis training was done in the field of the education and science development. In this field, literature has a role in language in order to be fundamental in supporting the students?óÔé¼Ôäó skill in analysing language in the scope of literature. Students need to have a skill in how they analysis the leterature that usually they find it in their daily life. This training had several steps; first, the introduction of literature. Secondly, introduction of mehod of reserach. Third, the application of literature in the real articles. And last, evaluation and improvement. So that, there should be a medium in accomodating the research of literature which are conducted by students of Indonesian Department. The evaluation of this traning was giving the material and practical analysis through the intensive guidance by lecturers as well as encouraging them to accomplish their final project (thesis).Key words; traning, language, literature